Attitudes About American Colleges 1990. A Survey Commissioned for National Higher Education Week - Gallup Organization, Inc., Princeton, NJ.; Gallup Organization, Inc., Princeton, NJ. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
A Gallup report presents the results and conclusions of a study designed to measure attitudes and perceptions among the nation's adults regarding higher education. The specific issues addressed cover the benefits of a college education to society at large, the focus of institutions of higher education, financial support of higher education institutions, and financial aid. The study, conducted in June 1990, involved 1,014 telephone interviews among a nationally representative sample of adults age 18 years and older. Among the study's findings are the following: (1) 75% felt that significant advancements in medicine and technology required more people attaining a college education; (2) 58% felt that having more college educated people would improve society's ability to solve problem areas such as crime, drug abuse, and homelessness; (3) conducting research and offering programs and financial assistance were areas believed to be needing more financial support; (4) 91% felt most students require financial aid in order to attend college; (5) 4% believed that what students borrow is too little; and (5) 66% believe financial aid from the federal government should be based on academic ability and financial need. A technical appendix accompanies the report. (GLR)
Availability: Council for Advancement and Support of Education, Suite 400, 11 Dupont Circle, Washington, DC 20036 (free).
Sponsoring Agency: Council for Advancement and Support of Education, Washington, DC.
ERIC Note: For the 1989 report, see ED 311 988.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adults; Attitude Measures; Audience Response; Educational Needs; Higher Education; Paying for College; Public Opinion; Role of Education; Student Financial Aid; Telephone Surveys; United States; Reports, Research